A quantitative flow visualization technique for on-site sport aerodynamics optimization - Sciacchitano, A.; Caridi, G.; Scarano, F. (Journal of Science and Cycling, 2015)
Aerodynamics plays a crucial role in cycling as in many other speed sports. Aerodynamic investigation is required primarily for two reasons: